2010
DOI: 10.5713/ajas.2010.90609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anion Supplementation on Growth Performance, Nutrient Digestibility, Meat Quality and Fecal Noxious Gas Content in Growing-finishing Pigs

Abstract: Forty-eight ((Duroc×Yorkshire)×Landrace) pigs with an average initial body weight (BW) of 48.47±1.13 kg were used in a 12-week growth trial to investigate the influence of Anion (silicate) supplementation on growth performance, nutrient digestibility, meat quality and fecal noxious gas content in growing-finishing pigs. Pigs were allotted into three dietary treatments in a randomized complete block design according to sex and initial BW. Each dietary treatment consisted of four replications with four pigs per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 23 publications
4
18
0
1
Order By: Relevance
“…Therefore, we investigated whether supplementation with AZ would exert positive effects on the growth performance of pigs. However, no significant effects on ADG, ADFI or feed efficiency of growing-finishing pigs were observed (Table 2), which is in agreement with the results reported by Chen et al (2005aChen et al ( , 2005b and Yan et al (2010). In contrast, a significant increase in feed conversion efficiency relative to the control was observed in pigs provided clinoptilolite supplemented diets (Mumpton and Fishman, 1977).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, we investigated whether supplementation with AZ would exert positive effects on the growth performance of pigs. However, no significant effects on ADG, ADFI or feed efficiency of growing-finishing pigs were observed (Table 2), which is in agreement with the results reported by Chen et al (2005aChen et al ( , 2005b and Yan et al (2010). In contrast, a significant increase in feed conversion efficiency relative to the control was observed in pigs provided clinoptilolite supplemented diets (Mumpton and Fishman, 1977).…”
Section: Resultssupporting
confidence: 87%
“…AZ had no significant effect on carcass quality grade and conformation grade of pork (Table 4), which is consistent with the results of a study conducted by Yan et al (2010). The toxic cation absorption capacity of zeolite prevented adverse effects on metabolic functions in hogs (Pond et al, 1993), resulting in no effect on carcass quality.…”
Section: Muscle Characteristics and Compositionsupporting
confidence: 92%
“…Similarly, Thacker [ 33 ] fed 0, 0.25, 0.5 or 0.75 % Biotite during the growing period and 0, 0.5, 1.0 or 1.5 % during the finishing period and observed no improvement in pig performance. Yan et al [ 34 ], fed the same composite clay as Yan et al [ 28 ] and found no improvement in growing-finishing pig performance. In addition, Lin et al [ 18 ], Yu et al [ 20 ], Poulsen and Oksbjerg [ 35 ], Shurson et al [ 36 ], Parisini et al [ 37 ], Abranches et al [ 38 ] and Han and Thacker [ 39 ] reported no improvements in pig performance as a result of dietary inclusion of clays.…”
Section: Introductionmentioning
confidence: 99%
“…Where improvements in pig performance have been noted, one of the most likely explanations for the improvement in performance is the fact that dietary clay supplementation has been shown to increase nutrient digestibility [ 8 , 9 , 27 , 28 , 34 37 ]. Li and Kim [ 27 ] reported that dietary supplementation with 0.5 and 1.0 % sericite increased the total tract digestibility of dry matter by 3.9 and 7.5 %, as well as the digestibility of nitrogen by 4.9 and 5.7 % for growing pigs (Table 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation